Histopathological study of heart and cardiac vessels in autopsy cases from tertiary health-care center - Kavitha Muniraj; Vincy TM; Teleflo Boopathy; Gowri Prakasam; Gowsalya Kannan (Asian Journal of Medical Sciences, 2024)
Background: Atherosclerosis is a chronic inflammatory disease causing more morbidity and mortality in developed as well as in developing countries. Among Indians, atherosclerotic lesions occur 10–15 years earlier, and the lesions are formed in the advanced stage. It is difficult and expensive to evaluate the atherosclerotic lesions in living subjects. Atherosclerosis of cardiac vessels and myocardial infarction are the most common fatal cardiac diseases discovered in autopsies. The incidence of coronary artery diseases is increasing worldwide as well as in India, which carries a huge challenge in diagnosing the same.